Roles of corn starch and gellan gum in changing of unconfined compressive strength of Shanghai alluvial clay - Jili Qu; Weiqing Qu; Guangping Li; Maimait Naman; Mengqing Zhang; Jinrui Cheng; Shouqian Wang; Jingyuan Yin (Science and Engineering of Composite Materials, 2024)
This article aims to study the effects of corn starch and gellan gum (gellan glue) on the unconfined compressive strength of alluvial soft clay in Shanghai. Firstly, starch and gellan gum were evenly mixed into Shanghai cohesive soil in a certain proportion, and soil samples were prepared according to the optimal water content. Secondly, the unconfined compressive strength test was carried out according to the content of corn starch, gellan glue, and curing time. The strength characteristics of Shanghai soft clay under various test conditions were studied. Finally, the software for statistics and drawing was used to perform regression analysis and drawing on the experimental data. The results showed that in the unconfined compressive strength test, when the curing time was 28 days, the starch content was 3% mixed with 0.5% gellan gum, the unconfined compressive strength of the sample was the highest, and generally, it seems that the strength keep increasing with curing time.